Multi-Omics Revealed the Protective Effects of Rhamnolipids in Lipopolysaccharide Challenged Broilers - Zhang, Ruiqiang; Shi, Xueyan; Chen, Yuqi; Liu, Jinsong; Wu, Yanping; Xu, Yinglei (Frontiers in Immunology, 2022)
Rhamnolipid (RL) is a glycolipid biosurfactant and exhibits the outstanding characteristics of strong antibacterial properties, low toxicity, and high biodegradability. Present research was conducted to explore the protective effects and mechanisms of rhamnolipids as an alternative to antibiotics in LPS (lipopolysaccharide)-challenged broilers. 16S rRNA gene sequencing and metabolomics were used for analyzing the cecal microbial composition and serum metabolites. Dietary antibiotics and RLS supplementation decreased the weight loss rate, enhanced serum immunoglobulins levels, reduced serum diamine oxidase and D-lactate acid concentration, improved the symptoms of intestinal bleeding and villus height, when broilers were challenged with LPS. The addition of RLS in the diet enhanced serum interleukin-4 and interleukin-10 contents, reduced serum interleukin-6 and tumor necrosis factor-α levels in LPS-challenged broilers compared with antibiotics group. The spearman's correlation analysis revealed that RLS may alleviate LPS-induced inflammatory responses through altering the 6-methoxymellein level in broilers. The genus Bacteroides may contribute to the decreased weight loss rate via regulating the serum lysoPC(20:5(5Z,8Z,11Z,14Z,17Z)) secretion. RLS alleviate LPS-induced intestinal injury, enhance the growth and immunity, ameliorate intestinal microflora and improve serum metabolites in LPS-challenged broilers. RLS exhibited better protective effect than antibiotic supplementation in the diet of LPS-challenged broilers. These findings provide potential regulation strategies and novel insights for RLS enhancing protective effect in LPS-challenged broilers.